Shear-wave amplitudes measured with cardiac MR elastography for diagnosis of diastolic dysfunction - Elgeti, Thomas; Knebel, Fabian; Haettasch, Robert; Hamm, Bernd; Braun, Juergen; Sack, Ingolf (Radiology, 2014)
Purpose: To test whether shear-wave amplitudes (SWAs) in the myocardium measured with cardiac magnetic resonance (MR) elastography enable diagnosis of myocardial relaxation abnormalities in patients with diastolic dysfunction. Materials and Methods: Each subject gave written informed consent to participate in this institutional review board-approved prospective study. Electrocardiographically triggered SWA-based cardiac MR elastography with 24.13-Hz external vibration frequency was performed in 50 subjects grouped into asymptomatic young (n = 10, 18-39 years) and asymptomatic old (n = 10, 40-68 years) subjects and patients with echocardiographically proved mild, moderate, or severe diastolic dysfunction (n = 30, 44-73 years). SWA images were analyzed in the left ventricular (LV) region and were normalized against reference SWA of the thoracic wall. Analysis of variance with Bonferroni-corrected pairwise comparison and Pearson correlation were used for statistical evaluation. Results: Young and old control subjects had normalized mean LV SWA of 0.67 ± 0.04 (standard error of the mean) and 0.56 6 0.04 (P =.18, F test), respectively. Compared with the control groups, patients with mild, moderate, and severe diastolic dysfunction displayed significantly reduced normalized mean LV SWA of 0.37 ± 0.04, 0.34 ± 0.04, and 0.29 ± 0.04 (P <.001, F test), respectively, which was inversely correlated to the severity of diastolic dysfunction (R = 20.61, P <.001). The best cutoff value to differentiate between asymptomatic volunteers and patients was 0.43, yielding an area under the receiver operating characteristic curve of 0.92, with 90% sensitivity and 89.7% specificity. Conclusion: LV SWA measured with cardiac MR elastography provides image contrast sensitive to myocardial relaxation abnormalities and shows significantly lower values in patients with diastolic dysfunction. © 2014 RSNA.
CRIS-Team Scopus Importer:2022-08-03